Does the grass snake (Natrix natrix) (Squamata: Serpentes: Natricinae) fit the amniotes-specific model of myogenesis? - Lewandowski, Damian (Protoplasma, 2016)
In the grass snake (Natrix natrix), the newly developed somites form vesicles that are located on both sides of the neural tube. The walls of the vesicles are composed of tightly connected epithelial cells surrounding the cavity (the somitocoel). Also, in the newly formed somites, the Pax3 protein can be observed in the somite wall cells. Subsequently, the somite splits into three compartments: the sclerotome, dermomyotome (with the dorsomedial [DM] and the ventrolateral [VL] lips) and the myotome. At this stage, the Pax3 protein is detected in both the DM and VL lips of the dermomyotome and in the mononucleated cells of the myotome, whereas the Pax7 protein is observed in the medial part of the dermomyotome and in some of the mononucleated cells of the myotome. The mononucleated cells then become elongated and form myotubes. As myogenesis proceeds, the myotome is filled with multinucleated myotubes accompanied by mononucleated, Pax7-positive cells (satellite cells) that are involved in muscle growth. The Pax3-positive progenitor muscle cells are no longer observed. Moreover, we have observed unique features in the differentiation of the muscles in these snakes. Specifically, our studies have revealed the presence of two classes of muscles in the myotomes. The first class is characterised by fast muscle fibres, with myofibrils equally distributed throughout the sarcoplasm. In the second class, composed of slow muscle fibres, the sarcoplasm is filled with lipid droplets. We assume that their storage could play a crucial role during hibernation in the adult snakes. We suggest that the model of myotomal myogenesis in reptiles, birds and mammals shows the same morphological and molecular character. We therefore believe that the grass snake, in spite of the unique features of its myogenesis, fits into the amniotes-specific model of trunk muscle development. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00709-016-1040-5) contains supplementary material, which is available to authorized users.